Tips for asking gender-responsive questions - Elias, Marlène; Bioversity International (Bioversity International, 2013)
This two-page publication highlights 15 key issues that researchers studying biodiversity management and conservation should bear in mind to formulate gender-responsive questions and conduct gender analyses. Attention to these issues will help researchers understand the gendered division of labour, gendered livelihoods, gendered access to and control over resources, and gendered decision-making processes that bear upon resource management and conservation processes in the regions where they work.